2022
DOI: 10.1002/ijc.33973
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol intake trajectories during the life course and risk of alcohol‐related cancer: A prospective cohort study

Abstract: Funding information MCCS cohort recruitment was funded by Cancer Council Victoria (https://www. cancervic.org.au/) and VicHealth (https:// www.vichealth.vic.gov.au/). The MCCS was further supported by Australian National Health and Medical Research Council (NHMRC) (https://www.nhmrc.gov.au/) grants 209057, 396414 and 1074383, and ongoing follow-up and data management has been funded by Cancer Council Victoria since 1995. Cases and their vital status were ascertained through the Victorian Cancer Registry and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…McDermott et al 10.3389/fdgth.2023.1178407 problematic in a rapidly changing technology field such as digital interventions. If systematic reviews are out-of-date the resulting review of reviews does not include the most recent evidence either.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…McDermott et al 10.3389/fdgth.2023.1178407 problematic in a rapidly changing technology field such as digital interventions. If systematic reviews are out-of-date the resulting review of reviews does not include the most recent evidence either.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Drinking behaviours amongst university and college students has also been shown to be highly concerning, with risky drinking being common place (5) and heavy drinking being reported in university students in high income countries (6)(7)(8). Increased consumption of alcohol in younger people has been linked to increased alcohol consumption in later adulthood (9) which in turn has also has been linked to increased risk of cancer (10).…”
Section: Introductionmentioning
confidence: 99%
“…The previously mentioned Australian study investigating alcohol consumption trajectories over the life-course also observed increased risks of alcohol-related cancers with similar estimates (45-94% increase). 6 However, the limited number of cancer cases in that study enabled specific evaluations of the association between alcohol consumption and only colorectal cancer. 6 We noted a significant cancer-risk elevation from light alcohol intake (≥10 g/day), which was previously reported for several cancers (including oropharyngeal, esophageal, and colorectal cancers).…”
Section: Discussionmentioning
confidence: 97%
“…6 However, the limited number of cancer cases in that study enabled specific evaluations of the association between alcohol consumption and only colorectal cancer. 6 We noted a significant cancer-risk elevation from light alcohol intake (≥10 g/day), which was previously reported for several cancers (including oropharyngeal, esophageal, and colorectal cancers). 4,5,24,25 A metaanalysis on lifetime alcohol consumption also supports our findings for upper aero-digestive tract and colorectal cancers.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation